Cultura de seguridad del paciente en enfermeros de atención primaria (2018)
Introduction: The promotion of patient safety culture is one of the main recommendations for the reduction of adverse events, particularly in the area of primary care, where its occurrence is not reported, generating risks for users who enter the health system. Objective: To identify the strengths and weaknesses of patient safety culture in primary care nurses and their relationship with sociodemographic variables. Methods: Correlation study with the participation of 41 primary care nurses. The Questionnaire Medical Office Survey on Patient Safety was translated, validated and adapted to Spanish. This questionnaire was self-applied at workplace. For the data analysis, the statistical package PAST version 3.08 was used and the chi-square tests of homogeneity were used for the qualitative variables, while Kruskal Wallis was used for the quantitative variables. Results: The overall score of patient safety culture was 51.21 %. The best-qualified dimensions were global quality scores and information exchange with other assistance services. Significant differences were found between the positive assessment of the high quality culture and variables such as age, academic level, years of work and weekly work hours. Conclusions: Patient safety culture was not categorized as either a strength or weakness. © 2018, Editorial Ciencias Medicas. All rights reserved.